2017
DOI: 10.18805/ajdfr.v36i02.7957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and time on some physical characteristics of Paneer whey

Abstract: The present investigation was to determine the various physical characteristics of paneer whey with respect to density, specific weight and electrical conductivity. These physical characteristics were determined considering three levels of temperatures 20, 25 and 30 o C at intervals of 1, 2 and 3 h. The highest values for density and specific weight of whey were observed 1015.43 kg/m 3 and 9.961 kN/m 3 at 20 o C respectively and with respect to time it was observed 1013.5 kg/m 3 and 9.942 kN/m 3 at 3 h respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…The values obtained for electrical conductivity of skim milk in the present study were within the ranges from 5.39 mS/cm to 5.66 mS/cm. Sahu et al (2017) observed that the highest value for electrical conductivity of paneer whey is 5.10 mS/cm at 30 0 C temperature with respect to time at 3 h is 4.93 mS/cm. Mabrook and Petty (2003) concluded that electrical conductivity of skim milk (0.1% fat and 4.9% lactose) is 5.4 mS/cm.…”
Section: Results and Discussion Effect Of Time And Temperature On Denmentioning
confidence: 86%
See 2 more Smart Citations
“…The values obtained for electrical conductivity of skim milk in the present study were within the ranges from 5.39 mS/cm to 5.66 mS/cm. Sahu et al (2017) observed that the highest value for electrical conductivity of paneer whey is 5.10 mS/cm at 30 0 C temperature with respect to time at 3 h is 4.93 mS/cm. Mabrook and Petty (2003) concluded that electrical conductivity of skim milk (0.1% fat and 4.9% lactose) is 5.4 mS/cm.…”
Section: Results and Discussion Effect Of Time And Temperature On Denmentioning
confidence: 86%
“…With increasing temperature decrease in viscosity is also associated with the lower cohesive forces between molecules. Sahu et al (2017) observed that the highest value for density of paneer whey is 1015.43 kg/m 3 at 20 o C, they concluded that increasing density with respect to decreasing temperature. From this analyzed data, it was recorded that the effect of temperature showed significant difference but effect of time and combined effect of temperature and time did not show significant effect on density of skim milk.…”
Section: Results and Discussion Effect Of Time And Temperature On Denmentioning
confidence: 95%
See 1 more Smart Citation